Monitoring biological degradation of historical stone using hyperspectral imaging - Eva Matoušková; Kateřina Kovářová; Michal Cihla; Jindřich Hodač (European Journal of Remote Sensing)
Stone is one of the most common materials used as a building material in central Europe for centuries. Historical objects are endangered by degradation procedures coming from physical, chemical and biological weathering agents.The weathering process itself should be analysed in detail in order to prevent historical objects by application of proper restoration cleaning techniques. Within our research, a historical sandstone block was analysed during time to monitor biological changes on the surface. The object of interest is situated in the immediate vicinity of Charles Bridge in Prague, which is protected as a UNESCO heritage site. This site was chosen due to high overall humidity all year long. For investigation of the year- round process of biodegradation hyperspectral sensor was used.  In the first place, data were processed using four vegetation indices (NDVI, RGRI, CRI1 and VREI1). All vegetation indices indicate that vegetation is thriving and subject to normal seasonal change. The second chosen method of data processing is to use spectral reflectance curves and their subsequence processing by Spectral Angle Mapper (SAM) classification algorithms. A decline in vegetation with the onset of autumn and during the winter months was detected.